Low Tensile Strength Suture With Transosseous Tunnels and Suture Anchors 5 mm in Diameter or Greater Are Associated With Higher Failure Rates in Primary Patellar Tendon Repair - Mark S. Katsma, D.O.; Vaughn Land, M.D.; S. Hunter Renfro, M.D.; Hunter Culp, M.D.; George C. Balazs, M.D. (Arthroscopy, Sports Medicine, and Rehabilitation, 2024)
Purpose: To determine the rate of and risk factors for clinical failure and return to military duty following primary patellar tendon repair with either transosseous trunnel repair or suture anchor repair. Methods: The Military Health System Data Repository (MDR) was queried to identify all adult patients undergoing surgical treatment of a patellar tendon rupture in the Military Health System from 2014 to 2018. Patients who underwent either transosseous tunnel repair or suture anchor repair were included. Health records were examined to collect additional data. Univariate analysis and multivariate logistic regression models were used to determine independent risk factors for rerupture. Results: A total of 450 knees in 437 patients were included. Transosseous tunnel repair was the most frequently used technique (314/450, 77%), followed by suture anchor repair (113/450, 25%). Rerupture occurred in 33 knees (7%). There was no difference in rerupture rate between transosseous tunnel repair and suture anchor repair (P = .15), and this result persisted within the multivariate logistic regression model. Among transosseous tunnel repairs, use of low tensile strength suture was an independent risk factor for repair failure (odds ratio [OR], 3.4; P = .016). Among suture anchor repairs, use of anchors 5.0 mm in diameter or greater (OR, 12.0; P = .027) was an independent risk factor for repair failure. Conclusions: There is no statistically significant difference in failure rate between transosseous tunnel repair and suture anchor repair in primary patellar tendon ruptures. However, the use of low tensile strength suture with transosseous tunnels and the use of suture anchors 5.0 mm in diameter or greater resulted in significantly higher failure rates. These data suggest that use of high tensile strength suture in transosseous tunnel repair and use of suture anchors less than 5.0 mm in diameter in suture anchor repair result in lower failure rate in primary patellar tendon repair. Level of Evidence: Level III, retrospective cohort study.